Characterization of metalliferous sediment from a low-temperature hydrothermal environment on the Eastern Flank of the East Pacific Rise - Bodeï, S.; Buatier, M.; Steinmann, M.; Adatte, Thierry; Wheat, C. G. (My University, 2008)
Metalliferous deposits are described from the eastern flank of the East Pacific Rise (EPR) offshore Costa Rica, close to a basaltic seamount called “Dorado high”. Based on heat-flow data and porewater profiles, the site is an area of active low-temperature hydrothermal discharge. We focus on the mineralogical and chemical analysis from a 124 cm long gravity core (GC50), located on the northwestern slope of the 100 m high Dorado. In this core, the sediments consist of detrital clay minerals as well as authigenic minerals such as zeolites, apatites, and Fe/Mn-rich oxyhydroxides. In contrast, the reference sediments from adjacent areas without hydrothermal activity are olive gray hemipelagic muds composed of volcanic glass particles, clay minerals, siliceous microfossils, and some detrital quartz and feldspar.
Bulk sediment chemistry and chemical enrichment factors calculated with respect to the reference sediment indicate that the most important chemical changes occurred at the base of the core from 100 to 124 cm bsf, with strong enrichments in MnO, CaO, P2O5, and Fe2O3. These enrichments are correlated with the occurrence of authigenic Fe-oxyhydroxide (goethite) and Mn oxide (todorokite and vernadite, at 100 cm bsf), and hydrothermal apatite (110–124 cm bsf). In the upper section of the core from 12 to 70 cm, the sediment is composed of abundant smectite and authigenic phillipsite, and only minor chemical changes can be observed with respect to the reference sediments.
The ubiquitous presence of phillipsite suggests that the entire sedimentary column of core GC50 was first affected by diagenesis. However, below 70 cm bsf, these phillipsites are partially dissolved and Fe oxides occur from 110 to 124 cm, followed upward by Mn oxides at 100 cm. This transition from Fe to Mn-rich sediments can be interpreted in terms of an upward increasing redox potential. PAAS-normalized REY patterns of GC50 sediments present clearly negative Ce and positive Y anomalies inherited from seawater at the base of core GC50. These anomalies decrease upward, which we interpret together with the transition from Fe to Mn-rich sediments by an upward migrating low-temperature hydrothermal fluid. Thus, after a first stage of diagenesis, the discharge of a low-temperature hydrothermal fluid occurred through the sedimentary column, leading to the precipitation of hydrothermal compounds that are lacking towards the surface.
Keywords: East Pacific Rise; ridge flank; hydrothermalism; alteration; metalliferous deposits; rare-earth elements